2009
DOI: 10.1007/s10571-009-9359-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis of Mitochondria in Aging PS-1 Transgenic Mice

Abstract: Accumulating evidence suggests mitochondrial alterations are intimately associated with the pathogenesis of Alzheimer's disease (AD). To determine if mutations of presenilin-1 (PS-1) affect levels of mitochondrial proteins at different ages we enriched mitochondrial fractions from 3, 6, 12 month old knock-in mice expressing the M146V PS-1 mutation and identified, and quantified proteins using cleavable Isotope Coded Affinity Tag (ICAT) labeling and two dimensional liquid chromatography/tandem mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 82 publications
0
26
0
Order By: Relevance
“…This phenomenon – that is, the accumulation of defective mitochondria and a corresponding decrease in mitochondrial function with the increase of age – has been observed: 1) in postmortem brains from patients with AD [36] and in transgenic mice with over-expressed amyloid precursor protein [42], and 3) in a presenilin 1 transgenic mouse model [43]. Briefly, Hirai et al [41] found an increase in damaged mitochondria and defective mtDNA, including increased mtDNA deletions in hippocampal and cortical neurons, from postmortem brains from AD patients, compared to the mtDNA in postmortem hippocampal and cortical neurons from healthy control subjects, indicating that mitochondrial abnormalities are evident in AD brains [36].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon – that is, the accumulation of defective mitochondria and a corresponding decrease in mitochondrial function with the increase of age – has been observed: 1) in postmortem brains from patients with AD [36] and in transgenic mice with over-expressed amyloid precursor protein [42], and 3) in a presenilin 1 transgenic mouse model [43]. Briefly, Hirai et al [41] found an increase in damaged mitochondria and defective mtDNA, including increased mtDNA deletions in hippocampal and cortical neurons, from postmortem brains from AD patients, compared to the mtDNA in postmortem hippocampal and cortical neurons from healthy control subjects, indicating that mitochondrial abnormalities are evident in AD brains [36].…”
Section: Discussionmentioning
confidence: 99%
“…Human AD brain displays evidence of decreased mitochondrial number and mitochondrial damage [147,148], decreased complex IV activity [149][150][151] and deletions in mitochondrial DNA correlate with impaired complex IV activity in human AD brain [152]. Transgenic mice modeling AD exhibit impaired mitochondrial function and reactive oxygen species (ROS)-related mitochondrial damage [147,153,154]. Indeed mitochondrial dysfunction is an early feature in transgenic AD mice (reviewed in [155]), as evidenced for example by impaired Ca 2+ uptake [156] and decreased complex IV activity [157] from 2 months of age.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…This isotope-labeling technology has been applied in several neuroscience projects such as the study of the influence of aging in the proteome of CSF (cerebrospinal fluid) [72], the study of differential mitochondrial proteins analysis in the pathophysiology of Parkinson's [73] or Alzheimer's diseases [74], and also to aid the study of the expression of synaptosomal protein in cerebral ischemia [75], migraine mouse models [76], or in the study of addiction [77].…”
Section: Chemical Labeling Approaches: Isotope Techniquesmentioning
confidence: 99%